Attitude of primary care physicians toward patient safety in Aseer region, Saudi Arabia - Yahia M Al-Khaldi (Journal of Family and Community Medicine, 2013)
Objective: The objective of this study was to assess the attitude of physicians at primary health-care centers (PHCC) in Aseer region toward patient safety. Materials and Methods: This study was conducted among working primary health-care physicians in Aseer region, Saudi Arabia, in August 2011. A self-administered questionnaire consisting of three parts was used; the first part was on the socio-demographic, academic and about the work profile of the participants. The attitude consisting of 26 questions was assessed on a Likert scale of 7 points using attitude to patients safety questionnaire-III items and the last part concerned training on "patient safety," definition and factors that contribute to medical errors. Data of the questionnaire were entered and analyzed by Statistical Package for the Social Sciences (SPSS) version 15. Results: The total number of participants was 228 doctors who represent about 65% of the physicians at PHCC, one-third of whom had attended a course on patient safety and only 52% of whom defined medical error correctly. The best score was given for the reduction of medical errors (6.2 points), followed by role of training and learning on patient safety (6 and 5.9 points), but undergraduate training on patient safety was given the least score. Confidence to report medical errors scored 4.6 points as did reporting the errors of other people and 5.6 points for being open with the supervisor about an error made. Participants agreed that "even the most experienced and competent doctors make errors" (5.9 points), on the other hand, they disagreed that most medical errors resulted from nurses′ carelessness (3.9 points) or doctors′ carelessness (4 points). Conclusion: This study showed that PHCC physicians in Aseer region had a positive attitude toward patient safety. Most of them need training on patient safety. Undergraduate education on patient safety which was considered a priority for making future doctors′ work effective was inadequate.